The therapeutic efficacy of 1-[4-(1,1,3,3-tetramethyl butyl) phenoxy]-3-(n-benzyl hexametylenimino)-2-propanol chloride in vivo - Suvorova, Zinaida (ScienceRise: Biological Science, 2017)
The aim of the research was to determine the therapeutic efficacy of the derivative of arilalifatic aminopropanols 1-[4-(1,1,3,3-tetramethyl butyl)phenoxi]-3-(N-benzyl hexamethylenimino)-2-propanol chloride (compound КВМ-194) in experiments in vivo on the model of the generalized infection, conditioned by Candida albicans. Methods. The experimental generalized infection was recreated on white nonlinear mice, using C. albicans 1486 strain. The infecting dose was 107 of fungal elements/animal. The efficacy of КВМ-194 was determined in the prophylactic, treating-prophylactic and treating regimes at intraoperational administration of the compound in doses 0,01 LD50 та 0,001 LD50. Results. It was established, that in the prophylactic regime of use at the intraoperational administration, the compound KVM-194 in a dose 0,001 LD50 favors survival of 50 % of animals, in a dose 0,01 LD50 - 100 % of infected animals (at 100 % death in the control). At the administration in the treating-prophylactic regime in a dose 0,01 LD50 this compound prevent death of 50 % of infected animals. The derivative of arilalifatic aminopropanols revealed the most expressed efficacy at the generalized candidiasis in the treating regime of use: at the administration of КВМ-194 in doses 0,001 LD50 and 0,01 LD50 death of experimental animals is absent (at 100 % of death in the control). Conclusions. The obtained data testify to the efficacy of the derivative of arilalifatic aminopropanols in low doses at generalized mycosis, conditioned by C. albicans, and prospects of the elaboration of an effective antifungal preparation on its base.